2015
DOI: 10.1007/s12517-015-2080-4
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability mapping of groundwater aquifer using SINTACS in Wadi Al-Waleh Catchment, Jordan

Abstract: This paper aims at evaluating the level of groundwater vulnerability to pollution in Wadi Al-Waleh wells and South Amman area based on SINTACS model. The Wadi AlWaleh Catchment (WWC) is considered to be one of the most important sub-basins in the middle part of Jordan. This study creates a map of groundwater vulnerability that shows areas with potential pollution. Areas are then classified into units with different levels of vulnerability based on anthropogenic and hydrogeological factors. The parameters of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…This information was processed into the Map of Groundwater Vulnerability to Pollution (Figure 3). The results are consistent with Al-Shatnawi et al (2016), who found that areas with medium vulnerability to pollution had a SINTACS index of 97-128.…”
Section: Sintacs Index Analysissupporting
confidence: 91%
“…This information was processed into the Map of Groundwater Vulnerability to Pollution (Figure 3). The results are consistent with Al-Shatnawi et al (2016), who found that areas with medium vulnerability to pollution had a SINTACS index of 97-128.…”
Section: Sintacs Index Analysissupporting
confidence: 91%
“…The large quantity and quality of available data allowed the application of the SINTACS method (Civita & De Maio, 2000) whose use has been validated for the Mediterranean areas (e.g. Al-Shatnawi et al, 2016). The parameters and sources of data considered as well as elaborations carried out for their estimation are described following.…”
Section: Methodsmentioning
confidence: 99%